1994
DOI: 10.1017/s0963180100005156
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Aspects of Nondisclosure

Abstract: A basic assumption in current western medicine is that good healthcare involves informed choices. Indeed, making informed choices is not only viewed as “good practice” but a right to which each individual is entitled, a perspective only recently developed in the medical field.Moreover, in the case of ethical decisions, much of the discussion on the role of the family is cast within the autonomy paradigm of contemporary bioethics; that is, family members provide emotional support but do not make decisions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 20 publications
0
40
1
Order By: Relevance
“…This justification falls under the traditional heading of therapeutic privilege. As well, patients are allowed to actively use their autonomy to defer disclosure to friends or family members if they state that they do not wish to know this information [22].…”
Section: Why We Disclose In the Usmentioning
confidence: 99%
“…This justification falls under the traditional heading of therapeutic privilege. As well, patients are allowed to actively use their autonomy to defer disclosure to friends or family members if they state that they do not wish to know this information [22].…”
Section: Why We Disclose In the Usmentioning
confidence: 99%
“…21 One study of 214 older adults with limited life expectancy (91% white) found that 50% of participants with a prognosis of 5 years left to live and 83% of those with a prognosis of less than 1 year wanted to discuss prognosis with their doctor. 22 Literature from outside the US shows that elders in traditional Chinese families may prefer nondisclosure of poor prognosis, 23,24 though more recent findings from China and Korea suggest that patient attitudes in Asian cultures may be changing in favor of direct, patient-centered disclosure. 25,26 A limited number of studies from the advance planning literature also point to Latinos' unique perspectives on patient-doctor discussions around the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to protect patients from the harm associated with knowing their diagnosis and prognosis, there is a need to keep information about the disease and prognosis from the patient and to release disease-related information only to patients' families (12)(13)(14). Furthermore, in Asian cultures a model of family autonomy is well-recognized in which family members have legitimate superior decision making authority even over fully competent patients (15,16). Physicians' respect for patient autonomy frequently is subordinate to the power of family (13)(14)(15).…”
mentioning
confidence: 99%